SELF-REFLECTION OF FAMILIES ON THEIR ABILITY TO CARE FOR INDIVIDUALS WITH SCHIZOPHRENIA: A DESCRIPTIVE STUDY - Iswanti, Dwi Indah; Nursalam; Rizki Fitryasari; Nia Agustiningsih; Kandar (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2025)
Introduction: The family's inability to care for schizophrenic patients can be caused by a lack of self-reflection in the form of self-control over the family's emotional expression, the desire to overcome care problems, and self-evaluation of the care that has been provided. Self-reflection is an inner resource in the family's ability to care for schizophrenia patients. The aim of the research is to describe the ability of family self-reflection to care for schizophrenic patients. Method: The research method uses a quantitative descriptive design using a cross-sectional approach. A sample of 135 families caring for schizophrenia patients was selected using purposive sampling. The variable are the family's self-reflection and ability in caring for schizophrenia patients. Data was collected using questionnaire adapted from the Pearline Mastery Scale (PMS) and then analyzed descriptively. Results: The research results show that family self-reflection abilities are still in the sufficient category in terms of the desire to overcome care problems (54.1%) and self-evaluation of care (64.4%). Conclusions: The family's low self-reflection ability can be improved by providing training and education through counseling.